Parasocial relationships: the role of implicit and explicit affiliation motivation in the maintenance of bonds with celebrities and fictional characters in lonely individuals - Ng, Jazzlyn Zi Qing (Nanyang Technological University, 2025)
The present study investigated the moderating effect of explicit and implicit need for affiliation (n Affiliation) on the relationship between loneliness and parasocial relationship (PSR) engagement with media figures, namely celebrities and fictional characters. We also explored whether PSR engagement is associated with relatedness need satisfaction. One hundred and twenty-six participants aged 18 to 54 participated in an online study which contained measures assessing implicit n Affiliation, levels of loneliness, explicit n Affiliation, relatedness need satisfaction, and the participants’ PSR engagement with a favourite media figure. Results revealed a significant association between higher levels of loneliness and greater PSR engagement. While high levels of explicit n Affiliation moderated the relationship between loneliness and PSR engagement, high levels of implicit n Affiliation did not. Consistent with the literature about explicit and implicit n Affiliation being separate constructs, this suggests that explicit n Affiliation is a better predictor of engaging in PSRs than implicit n Affiliation — likely because PSR engagement is a more deliberate and conscious process. Although non-significant, we found that greater engagement in PSR is linked to lower relatedness need satisfaction, suggesting that overreliance on PSRs alone may not be a healthy or sufficient coping mechanism for loneliness. The findings of this study contribute to the literature in understanding how emotions and motivation affect the intensity of individuals engaging in PSRs with celebrities and fictional characters.